Perbedaan Peningkatan Berat Badan Sebagai Efek Samping Pemakaian Kontrasepsi Hormonal - Puspita, Irma Maya (Universitas Muhammadiyah Surabaya, 2022)
Objective: Hormonal contraception can affect weight gain, but the dose of hormones contained in combination pills and injections contraceptive is so small that there is almost no influence on body weight. The aim of this study was to determine the differences in weight gain as a side effect of hormonal contraception on combination pills and injections contraceptive acceptors.Methods: The design of this study is a comparative study in which combination hormonal contraception is the independent variable and weight gain is the dependent variable. The sample in the study was taken by simple random sampling, while the population in this study were all acceptors of hormonal contraceptive pills and combination injection in Langkap village, Burneh sub-district with 151 acceptors. Data collection techniques used documentation, statistical test using chi-square and considered significant at 0,05.Results: The results showed that p <Î± (0,02 <0,05). This means that HO is rejected and H1 is accepted, so there is a difference in weight gain as a side effect of hormonal contraceptives for combination pill and combination injection contraceptive acceptors.Conclusion: With these results, the authors hope that people should choose contraception that is most suitable for themselves so that they can reduce complaints and side effects while using certain contraceptives.